2010
DOI: 10.1111/j.1432-2277.2010.01191.x
|View full text |Cite
|
Sign up to set email alerts
|

Robotic renal transplantation: first European case

Abstract: A kidney from a 56-year-old mother was transplanted to her 37-year-old daughter laparoscopically using the daVinci HDSi surgical system. The kidney was introduced into the abdomen through a 7-cm suprapubic incision used also for the uretero-vescical anastomosis. Vascular anastomoses were carried out through a total of three additional ports. Surgery lasted 154 min, including 51 min of warm ischemia of the graft. Urine production started immediately after graft reperfusion. Renal function remains optimal at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
67
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 105 publications
(71 citation statements)
references
References 29 publications
2
67
0
2
Order By: Relevance
“…To our knowledge, this is the first reported attempt to analyze key factors of this procedure in a preclinical setting. Groups who first performed this procedure in patients did not report previous in vivo experimental attempts 9, 10, 16. A first important difference that we observed was the increase of the anastomosis time in the robot‐assisted transplantation group.…”
Section: Discussionmentioning
confidence: 77%
“…To our knowledge, this is the first reported attempt to analyze key factors of this procedure in a preclinical setting. Groups who first performed this procedure in patients did not report previous in vivo experimental attempts 9, 10, 16. A first important difference that we observed was the increase of the anastomosis time in the robot‐assisted transplantation group.…”
Section: Discussionmentioning
confidence: 77%
“…The main limitations of current dVss are lack of haptic feedback, high cost, risk of technical failure, poor adaptability to multiquadrant surgery, and loss of direct contact between surgeon and patient [10].…”
Section: Discussionmentioning
confidence: 99%
“…Other main drawbacks are risk of technical failure, loss of direct contact between surgeon and patient, and poor adaptability to multi-quadrant surgery [10].…”
Section: The Da Vinci Surgical Systemmentioning
confidence: 99%
“…With no available ideal cooling technique, some laparoscopic or roboticassisted kidney transplants have been experimentally or clinically performed under warm ischemia conditions without additional renal graftcooling procedures by some professors who anticipate that this issue will be extensively debated, and who expects it to provide new impetus to research. 4,7,9,10 In the series by Meraney, intracorporeal hypothermia was achieved by intra-arterial perfusion of ice-cold solution through a 4-F balloon catheter, 3 but the possible risks of vascular injury and issues of technical complexity were its drawbacks. Rosales and associates reported that renal hypothermia was maintained by means of ice and continuous transcutaneous irrigation with cold saline solution in their laparoscopic kidney transplant.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11] The hindrance in laparoscopic kidney transplant is not only that of technical demand, but also of intraoperative renal hypothermia, which has not yet been solved. On the other hand, the reported cases of laparoscopic or robot-assisted kidney transplant were performed heterotopically into the iliac fossa.…”
Section: Introductionmentioning
confidence: 99%